2001
DOI: 10.1074/jbc.r100008200
|View full text |Cite
|
Sign up to set email alerts
|

How Membranes Shape Protein Structure

Abstract: Constitutive ␣-helical membrane proteins (MPs) 1 are assembled in membranes by means of a translocation/insertion process that involves the translocon complex (1). After release into the membrane's bilayer fabric, a MP resides stably in a thermodynamic free energy minimum (evidence reviewed in Refs. 2 and 3). This means that the prediction of MP structure from the amino acid sequence is fundamentally a problem of physical chemistry, albeit a complex one. Physical influences that shape MP structure include in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
229
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(241 citation statements)
references
References 68 publications
10
229
0
1
Order By: Relevance
“…The authors (Tolleter et al, 2007) observed no structural transition when the protein was exposed to lipid membranes in aqueous media; however, this is not contrary to our observations and might be expected, since the membranes were composed of neutral phospholipids, not anionic phospholipids, which for DHN1 at least are essential to membrane binding. There are indeed many examples of interactions between amphipathic a-helices and membranes that are sensitive to polarity and charges at the membrane interface and to the distribution of charged amino acid residues on helical peptides (Mishra and Palgunachari, 1996;White et al, 2001). At low water potential, columbic interaction increases due to a diminished effect of the dielectric constant of water.…”
Section: Discussionmentioning
confidence: 99%
“…The authors (Tolleter et al, 2007) observed no structural transition when the protein was exposed to lipid membranes in aqueous media; however, this is not contrary to our observations and might be expected, since the membranes were composed of neutral phospholipids, not anionic phospholipids, which for DHN1 at least are essential to membrane binding. There are indeed many examples of interactions between amphipathic a-helices and membranes that are sensitive to polarity and charges at the membrane interface and to the distribution of charged amino acid residues on helical peptides (Mishra and Palgunachari, 1996;White et al, 2001). At low water potential, columbic interaction increases due to a diminished effect of the dielectric constant of water.…”
Section: Discussionmentioning
confidence: 99%
“…Because the physical forces that drive folding can change with environment, proteins in different cellular locations can be subject to distinct evolutionary constraints. Membrane proteins, in particular, must accommodate to a dramatically varied environment, ranging from hydrocarbon chains in the bilayer core to water as they emerge from the membrane (8,9). It therefore seems possible that distinct structural imperatives found in different environments could be an important contributor to evolutionary rates.…”
mentioning
confidence: 99%
“…These properties are also expected to modulate the thermodynamic stability of membrane proteins because the membrane environment imposes very different mechanical constraints (6, 7) on membrane proteins than water does on soluble proteins (8). A thorough understanding of the factors that determine the stability of membrane proteins is of fundamental theoretical interest to understand the forces that shape these proteins (9). Accurate assessments of their thermodynamic stability will also aid in the design of more stable membrane proteins for therapeutic applications and for structural studies of this structurally underrepresented class of proteins.…”
mentioning
confidence: 99%